Interleukin-1 Drives Cerebrovascular Inflammation via MAP Kinase-Independent Pathways - Thornton, Peter; W. McColl, Barry; Cooper, Laura; J. Rothwell, Nancy; M. Allan, Stuart (Current Neurovascular Research, 2010)
Cerebrovascular inflammation is triggered by diverse central nervous system (CNS) insults and contributes to disease pathogenesis. The pro-inflammatory cytokine interleukin (IL)-1 is central to this cerebrovascular inflammatory response and understanding the underlying signalling mechanisms of IL-1 actions in brain endothelium may provide therapeutic targets for disease intervention. For the first time, we compare the contributions of p38, JNK and ERK mitogen-activated protein (MAP) kinase and NF-κB pathways to IL-1-induced brain endothelial activation. In cultures of primary mouse brain endothelium and the rat brain endothelial GPNT cell line, interleukin-1β (IL-1β) induced a rapid (within 5 minutes) and transient activation of p38 and JNK (but not ERK) MAP kinases. IL-1β also induced nuclear recruitment of nuclear factor (NF)-κB p65. IL-1β-induced brain endothelial expression of intercellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM)-1 was insensitive to MAP kinase inhibitors. IL-1β-induced brain endothelial expression of ICAM-1 and VCAM-1 was inhibited (80-88 %) by the proteasome inhibitor MG132 or the antioxidant caffeic acid phenethyl ester (CAPE), effects suggested to be NF-κB-dependent. IL-1β-induced brain endothelial CXCL1 expression was partially inhibited by JNK MAP kinase or MG132 (62 or 56 %, respectively). However, CXCL1 secretion from brain endothelium was reduced (65 %) only by MG132, and not MAP kinase inhibitors. Similarly, IL-1β-induced neutrophil transendothelial migration was reduced (77-89 %) by MG132, but not MAP kinase inhibitors. In summary, we show that several key components of IL-1β-induced brain endothelial activation (CAM, CXCL1 expression or release and neutrophil transmigration) are largely independent of MAP kinase activity but are reduced by proteasome inhibition, possibly reflecting a requirement for NF-κB activity. Similar mechanisms may contribute to cerebrovascular inflammation in response to CNS injury.
Keywords: MG132